Bagian Depan Agrotrop : Journal on Agriculture Science Vol. 12, No. 2, November 2022 - Pengelola AGROTROP (Agrotrop : Journal on Agriculture Science, 2022)
Bagian Depan Agrotrop : Journal on Agriculture Science Vol. 12, No. 2, November 2022